Muscles force and joints load simulation of bicycle riding using multibody models - Liu, Y. S.; Tsay, T. S.; Wang, T. C. (Procedia Engineering, 2011)
A three dimensional multibody dynamic numerical model using LifeMOD and ADAMS is presented to simulate and analyze the load of wrists, shoulders, leg muscles, knees, and ankles of bicycle riding. Applications of ADAMS/LifeMOD are widely used, for example, rifle shot stress to the human body, golf swing, Tae Kwon Do side kick simulation, rowers paddle boat. Applications are even in the medical research including dynamic stability of human spine simulation, and thoracic and lumbar dynamic simulation. Vertical (height) and horizontal position of bicycle saddle are adjusted in the three dimensional multibody model to simulate muscles force for city bicycle riding and race bicycle riding. Besides, loads of shoulders, wrists, knees, and ankles are analyzed between postures of city bicycle riding and race bicycle riding. The objective of this research is to obtain a suitable posture either for city bicycle riding or race bicycle riding to prevent sports injuries. ADAMS/LifeMOD simulation of riding city bicycle and race bicycle with different riding postures is presented in this paper. Several main findings include: (1) If the bicycle saddle is too high, soleus force would be increased. (2) If the bicycle saddle is too low, biceps femoris and iliacus forces would be increased. (3) The influence on muscles force caused by a little adjustment of distance between saddle and handlebars may be ignored. (4) Posture of riding race bicycle bends upper body more and increases iliacus forces but decreases soleus force. (5) Because race bicycle riding posture bends upper body, the joints loads on lumbar, shoulders and elbows are greatly increased.